The effect and approach of dentures on the nutritional state of the elderly - Binhuraib, Haitham Mohammed; Alwathnani, Somaya Saad; Alanazi, Asma Gadan; Alqaidy, Manal Yahya; Aljarallah, Abdulaziz Abduallah; Alqurashi, Nashwa Saud; Alreshidi, Faisal Abdullah; Aldakkan, Bayan Ahmad; Alazmi, Awadh Owaidh; Sulimani, Asim Adnan; Alanazi, Nowair Ali (International Journal Of Community Medicine And Public Health, 2023)
The absence of natural teeth presents considerable hurdles in consuming certain foods that demand efficient chewing, rendering elderly individuals vulnerable to malnutrition. Studies have reported malnutrition rates among this group ranging from 2% to 10%. Several factors contribute to this issue, including tooth loss itself, diminished masticatory function, and age-related alterations in taste sensitivity and saliva production. This review delves into the significant effect of dentures on the nutritional well-being of elderly individuals, shedding light on the challenges posed by edentulism, or complete tooth loss. The review underscores the crucial role of integrating dietary guidance into the prosthodontic treatment of edentulous patients. Personalized dietary counselling emerges as a vital strategy to rectify nutrient imbalances and enhance oral and overall health. Key recommendations encompass embracing a diverse array of foods while also moderating salt, fat, and sugar consumption. Furthermore, promoting the intake of hydrating fluids such as water, juice, and milk is essential. Continuous monitoring and support are emphasized as indispensable components for ensuring enduring dietary improvements among this vulnerable population. In conclusion, this review underscores the imperative of addressing the nutritional implications of dentures in the elderly and advocates for a comprehensive approach to safeguarding their dietary health.